Adherence self-efficacy, interpersonal forgiveness and perceived social supports as nexus of subjective well-being among people living with hiv /aids in Akwa-Ibom, Nigeria (2019)
Correlational design was adopted to investigate the relationship among adherence self- efficacy, interpersonal forgiveness and perceived social support on subjective-well-being of PLWHA in Akwa-Ibom state. Purposive sampling technique was used to select one hundred persons living with HIV and AIDS from the state chapter of Network of People Living with HIV/AIDS in Nigeria (NEPWHAN) made of fifty-six males and forty-four females with age ranging from 18-to 45 years and mean age of 31.5. They responded to four self-report measures. Pearson Product Moment Correlation (PPMC), t-test for independents samples and multiple regressions were utilised to analysis three questions. Results show that independent variables have linear relationship with the subjective well-being of respondents. Further, interpersonal forgiveness was most potent in predicting subjective well-being (fi = 0.464, t = 6.011, P < 0.05) followed by perceived social support (fi = 0.233, t =3.898, P < 0.05), while the least was adherence self- efficacy (P = 0.053, t = 0.707, P >0.05). It was concluded that subjective well-being is associated with personal and socio-psychological factors. The theoretical and practical implications of the findings were discussed.